How Did the Neoclassical Paradigm Conquer a Multi-disciplinary Research Institution? - Olivier Godechot (Revue de la Régulation)
The paper analyses the social conditions of a disciplinary evolution and paradigmatic shift. It is based on the history of economics at the EHESS from 1948 to 2005. An analysis of the PhD committees database enables us to trace the importance and evolution of different economic paradigms within this institution. In the early eighties, the traditional interdisciplinary humanist economics was challenged by a new generation of neoclassical engineer-economists. Far from being a mere declination of a general trend in the discipline, this paradigmatic shift was largely contingent, resting on local context and the influence of a few key persons. The exhibition of international capital and the building of political alliances within the assembly were also key elements for the change and for the survival of the new lineage in a rather hostile environment.